2018
DOI: 10.1111/cge.13134
|View full text |Cite
|
Sign up to set email alerts
|

Novel spondyloepimetaphyseal dysplasia due to UFSP2 gene mutation

Abstract: Beukes hip dysplasia is an autosomal dominant disease which has to date been described only in a large South African family of Dutch origin. The patients presented with progressive epiphyseal dysplasia limited to femoral capital epiphysis and their height was not significantly reduced. A unique variant of the ubiquitin‐fold modifier 1 (Ufm1)‐specific peptidase 2 (UFSP2) gene (c.868T>C) has been reported in all individuals from Beukes family with clinical and radiological diagnosis of Beukes hip dysplasia. Thre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
27
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 8 publications
2
27
0
Order By: Relevance
“…The robust association of human UFMylation genes with abnormal brain development and microcephaly in humans (3,11,23,43) and with defective neuromuscular junction formation in Drosophila (12) suggests a role for UFMylation in tissue development, a process that is intimately dependent on cell-cell and cell-matrix interaction. In this regard, it is especially noteworthy that rare allelic variants of DDRGK1 (13) and UFSP2 (14,15) are linked to human skeletal dysplasias affecting cartilage development and that DDRGK1 deficiency is associated with impaired cartilage development in zebrafish and with delayed chondrogenesis in the mouse (13).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The robust association of human UFMylation genes with abnormal brain development and microcephaly in humans (3,11,23,43) and with defective neuromuscular junction formation in Drosophila (12) suggests a role for UFMylation in tissue development, a process that is intimately dependent on cell-cell and cell-matrix interaction. In this regard, it is especially noteworthy that rare allelic variants of DDRGK1 (13) and UFSP2 (14,15) are linked to human skeletal dysplasias affecting cartilage development and that DDRGK1 deficiency is associated with impaired cartilage development in zebrafish and with delayed chondrogenesis in the mouse (13).…”
Section: Discussionmentioning
confidence: 99%
“…Homozygous disruption of the UFM1 pathway in mice causes midgestation embryonic lethality associated with impaired hematopoiesis (2,(8)(9)(10). In humans, hypomorphic loss-offunction alleles of genes that code for UFM1, UBA5, or UFPS2 are linked to diverse pathologies, including leukodystrophy (3), epileptic encephalopathy (11), spinocerebellar ataxia (12), and skeletal abnormalities (13)(14)(15), revealing an essential role for UFMylation in multiple organ systems. Although several cellular proteins have been reported to be UFMylation targets (5,7,(16)(17)(18), none of these have been demonstrated to form covalent adducts with UFM1 under physiological conditions and none have been plausibly linked to the cellular or organismal pathophysiologies associated with loss-of-function UFMylation mutants in humans or experimental animals.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, MRE11 mutations were detected in various tumors, but the underlying pathologic mechanisms were unclear (38,40,41). Some components of the UFMylation cascade were also reported to be dysfunctional in several types of cancers (10,42–44), but the UFMylation substrates and the involved signaling pathway remain unidentified. Here, we showed that a pathogenic MRE11(G285C) mutation detected in uterine endometrioid carcinoma (TCGA database) exhibited a similar cellular phenotype with the UFMylation-defective mutant MRE11(K282R) (Figures 7 and 8), suggesting that the role of the MRE11 UFMylation is closely associated with tumorigenesis.…”
Section: Discussionmentioning
confidence: 99%
“…BHD is an autosomal dominant disorder characterised by bilateral dysmorphism that is limited to the proximal femur and delayed ossification of the secondary centre, which results in severe progressive degenerative osteoarthropathy from childhood. A second novel mutation in the UFSP2 gene, also predicted to cause loss of UFSP2 catalytic activity [2] has been identified in affected members of a family with a novel form of autosomal dominant spondyloepimetaphyseal dysplasia (SEMD) involving the epiphyses predominantly of the hips, but also of knees, ankles, wrists and hands, with variable degrees of metaphysis and spine involvement and characterised by short stature, joint pain and genu varum.…”
Section: Introductionmentioning
confidence: 99%